Jenny Thompson's Full Stroke (Non-breathing) at 80 m of Her Leg of the Gold Medal 4 x 100 m Medley Relay Race at the 1998 Perth World Championships - Rushall, B. S. (1999)
Video pictures (11 frames) and the appropriate technical/ biomechanical explanations for Jenny Thompson's Full Stroke (Non-breathing) at 80 m of Her Leg of the Gold Medal 4 x 100 m Medley Relay Race at the 1998 Perth World Championships. Jenny Thompson's stroke continues to have deficiencies at entry. The narrow entry and outward scull do not contribute to propulsion and contribute to unnecessary body movements and deterioration in streamline. These movements should be compared to those of Mary T. Meagher and the efficiencies compared. It is this writer's opinion that the differences exhibited between Jenny Thompson's breathing and non-breathing strokes are due to breathing and not fatigue.